Pengelolaan sampah melalui pemilahan dan jadwal pembuangan sampah rumah tangga sebagai upaya penegakkan hukum lingkungan di Indonesia - Kalalo, Flora P.; Pontoh, Kathleen Catherina; Pangemanan, Arcelinocent E. (Fakultas Hukum Universitas Bangka Belitung, 2020)
The waste problem in Indonesia have become a national problem, nowdays the management and handling of household waste in Cities of Indonesia was not environmentally sound and not equitable social, some of the causes are the regulation and handling was not pro-environment and also not accompanied by participation of entire community. The implementation of Act No. 18 of 2008 about Waste Management not maximum running because law enforcement can not encourage the society to behave environmental conception in the management of waste based on maintenance and protection of environmental principal. The research method used is legal research using a statutory and conceptual approach. The management and handling of household waste should be sorting of waste based on the characteristic method and disposal schedule. These activity starting from household will forming the role and encourage the society to participate and handle their household waste. The result aims to reduce the amount of household waste. Keywords : Law enforcement, disposal schedule, sorting, household, waste.